The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1128/jvi.02682-05
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the EBNA1 Epstein-Barr Virus Protein by Serine Phosphorylation and Arginine Methylation

Abstract: The Epstein-Barr virus (EBV) EBNA1 protein is important for the replication and mitotic segregation of EBV genomes in latently infected cells and also activates the transcription of some of the viral latency genes. A Gly-Arg-rich region between amino acids 325 and 376 is required for both the segregation and transcriptional activation functions of EBNA1. Here we show that this region is modified by both arginine methylation and serine phosphorylation. Mutagenesis of the four potentially phosphorylated serines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 69 publications
1
56
0
Order By: Relevance
“…Factors that could alter the transport of the PIC to the nucleus did not overcome the p12-PM14 defect. Insertion of nuclear localization sequences (NLS), including the classical SV40 T antigen (TAg) NLS and the nonclassical KSHV LANA NLS (LANA [24][25][26][27][28][29][30][31][32] ), did not rescue MuLV p12-PM14, and neither showed tethering to the mitotic chromatin (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…Factors that could alter the transport of the PIC to the nucleus did not overcome the p12-PM14 defect. Insertion of nuclear localization sequences (NLS), including the classical SV40 T antigen (TAg) NLS and the nonclassical KSHV LANA NLS (LANA [24][25][26][27][28][29][30][31][32] ), did not rescue MuLV p12-PM14, and neither showed tethering to the mitotic chromatin (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…Such regions could provide molecular flexibility, allowing for rapid association/dissociation, promiscuity in partner interactions and increased availability to modification (66)(67)(68). Proteins with signalling or transcriptional regulatory functions appear to be enriched with intrinsically disordered segments, probably because this permits a greater repertoire of specific interactions (69).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, segregation of FR-containing plasmids in yeast was also achieved by expressing a single protein in which the EBP2 chromosomebinding domain was fused to the EBNA1 DNA-binding domain (Kapoor and Frappier, 2003). The importance of EBP2 for EBNA1-mediated segregation in human cells was suggested by the close correlation of effects of point mutations in residues 325-376 on plasmid-maintenance activity and EBP2 binding (Shire et al, 2006), and further confirmed by the finding that silencing of EBP2 in four different human cells lines (including EBV-positive cells) led to a substantial decrease in the association of EBNA1 with metaphase chromosomes (Kapoor et al, 2005). As expected, this loss of EBNA1 from the mitotic chromosomes was accompanied by a similar loss of oriP plasmids from the chromosomes (Kapoor et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that this interaction can be detected by yeast two-hybrid assay and that residues 325-376 are important for this interaction (Shire et al, 1999;Shire et al, 2006). We have now used a more sensitive version of this assay based on LexA fusion proteins, to evaluate whether EBNA1 N-terminal sequences also contribute to EBP2 interactions (Fig.…”
Section: Relationship Between Ebp2 Binding and Mitotic Chromosome Attmentioning
confidence: 99%
See 1 more Smart Citation